Protocol for Bone Augmentation with Simultaneous Early Implant Placement: A Retrospective Multicenter Clinical Study - Peter Fairbairn; Minas Leventis (Hindawi Limited, 2015)
Purpose. To present a novel protocol for alveolar bone regeneration in parallel to early implant placement. Methods. 497 patients in need of extraction and early implant placement with simultaneous bone augmentation were treated in a period of 10 years. In all patients the same specific method was followed and grafting was performed utilizing in situ hardening fully resorbable alloplastic grafting materials consisting of β-tricalcium phosphate and calcium sulfate. The protocol involved atraumatic extraction, implant placement after 4 weeks with simultaneous bone augmentation, and loading of the implant 12 weeks after placement and grafting. Follow-up periods ranged from 6 months to 10 years (mean of 4 years). Results. A total of 601 postextraction sites were rehabilitated in 497 patients utilizing the novel protocol. Three implants failed before loading and three implants failed one year after loading, leaving an overall survival rate of 99.0%. Conclusions. This standardized protocol allows successful long-term functional results regarding alveolar bone regeneration and implant rehabilitation. The concept of placing the implant 4 weeks after extraction, augmenting the bone around the implant utilizing fully resorbable, biomechanically stable, alloplastic materials, and loading the implant at 12 weeks seems to offer advantages when compared with traditional treatment modalities.